Human behavior and the social environment. Micro level. Individuals and families. 2nd ed. - van Wormer, Katherine (New York, 2010)
"While social work policy can be considered the what , and practice, the how , the study of human behavior is concerned with why . Why do people do the things they do? Why do individuals behave differently in groups than when alone? Why do some people become the victims of their lives while others who have endured tragedy become life's heroes?